Major and Trace Elements of Baobab Leaves in Different Habitats and Regions in Sudan: Implication for Human Dietary Needs and Overall Health - Abdelhakam Esmaeil Mohamed Ahmed; Massimo Mozzon; Ali Omer; Ayaz Mukarram Shaikh; Béla Kovács (Foods, 2024)
The metabolic needs of the human body and preventing infections require a diet with sufficient amounts of essential nutrients. This study aimed to investigate the importance of Baobab (Adansonia digitata L.) dried leaves as a healthy food source by determining the content of macro and trace elements in different habitats and regions. This study was conducted in Sudan and covered three different habitats, wetland (W), plainland (P), and mountain (M), in two regions (Blue Nile and Kordofan). The dry matter (DM) of Baobab leaves was considered for analyzed menials, and the results showed that the mean values were significantly affected by habitats where Baobab trees grew. The highest contents of potassium K (1653 ± 34 mg/100 g) and sodium (Na) 7.67 ± 1.18 mg/100 g were found in the W zone, whereas the highest contents of calcium (Ca) 2903 ± 187 mg/100 g and magnesium (Mg) 529 ± 101 mg/100 g were detected in the M and P zones, respectively. In addition, the two regions showed significant differences in trace and macro elements, i.e., higher levels of iron (Fe) 17.17 ± 2.76 mg/100 g and magnesium (556 ± 55 mg/100 g) were found in the Kordofan region while higher levels of zinc (Zn) 2.548 ± 0.55 mg/100 g and calcium (2689 ± 305 mg/100) were in the Blue Nile region. These varying amounts of elements can be used in our daily diets because of their potentially healthy effects, especially in areas where access to nutrient-rich foods is limited.